Treatment Supporters And Level Of Health Facility Influence Completion Of Sputum Smear Monitoring Among Tuberculosis Patients In Rural Uganda: A Mixed-Methods Study - Izudi, Jonathan; Tamwesigire, Imelda K.; Bajunirwe, Francis (International Journal of Infectious Diseases, 2020)
To investigate whether treatment supporters influence the completion of sputum smear monitoring (SSM) among adult persons with bacteriologically confirmed pulmonary tuberculosis (BC-PTB), and to explore the reasons for incomplete SSM according to healthcare workers, persons with BC-PTB, and their treatment supporters in rural eastern Uganda.A mixed-methods design was used. Quantitative data were abstracted from tuberculosis unit registers, while qualitative data were obtained through key informant interviews with healthcare workers and in-depth interviews with persons with BC-PTB and their treatment supporters. Quantitative data were analyzed with Stata. Qualitative data were transcribed verbatim and analyzed using a thematic content approach.Records were abstracted for 817 patients. Of these, 226 (27.7%) completed SSM. Factors independently associated with SSM completion included having a treatment supporter (adjusted risk ratio (ARR) 2.40, 95% confidence interval (CI) 1.23–4.70), treatment at a district hospital (ARR 1.61, 95% CI 1.04–2.49), treatment at a regional referral hospital (ARR 2.00, 95% CI 1.46–2.73), and every additional year since 2015 (ARR 1.29, 95% CI 1.17–1.43). Reasons for incomplete SSM related to health system, patient, treatment supporter, and healthcare provider factors.Completion of SSM was low. Persons with BC-PTB who have a treatment supporter were more likely to complete SSM compared to those without, and those receiving treatment at higher level facilities were more likely to complete SSM compared to those at lower level ones.
Keywords: Bacteriologically confirmed pulmonary tuberculosis; Smear-positive pulmonary tuberculosis; Sputum smear completion; Sputum smear monitoring; Treatment success rate